BOOSTING ORGANIC RICE FARMER COMPETENCY THROUGH ORGANIC PESTICIDE PRODUCTION TRAINING IN SUMPIUH VILLAGE BANYUMAS DISTRICT - Zulkifli, Lutfi; Soesanto, Loekas; Rachmah, Malinda Aptika; Ilma, Ajeng Faizah Nijma; Budiyoko, Budiyoko (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
The Gatos Farmers Group in Sumpiuh Village, Banyumas District, has consistently cultivated organic rice over the past two years. This initiative was driven by awareness of the negative impacts of conventional rice farming, particularly the use of chemical inputs, on both the environment and human health. As part of the support provided to the organic rice cultivation efforts of the Gatos Farmers Group, this community service program involved organic pesticide production training and pratice, aimed to enhance farmers' knowledge and equip them with technical skills to produce organic pesticides using natural materials readily available in their surroundings. The training began with participatory planning, followed by lectures on the subject, and continued with hands-on practice in making organic pesticides. The training successfully improved farmers' knowledge of organic pesticides, as evidenced by the increase in post-test scores compared to pre-test scores, further validated through statistical testing using a paired sample t-test. Post-training monitoring indicates that members of the Gatos Farmers Group have adopted organic pesticide production and applied it to their rice farming.